Consignment of Disputed Land in Land Acquisition for the Development and Revitalization of Balohan Port, Sabang - Riyan Zulfa Rizki; Ilyas Ismail; Muhammad Insa Ansari (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Land acquisition for public purposes is intended to ensure land availability for development while safeguarding the rights of affected parties through fair and equitable compensation as regulated under Law Number 2 of 2012 and its implementing regulations. However, disputes over land ownership often prevent direct payment of compensation, thereby necessitating the use of a consignment mechanism through the court. This study examines the implementation of consignment for disputed land and analyzes the legal standing and fulfillment of rights of both the prevailing and losing parties in the land acquisition process for the development and revitalization of Balohan Port, Sabang. The research addresses the problem of how compensation is secured and distributed when ownership remains contested, and whether the mechanism ensures legal certainty and justice for all parties involved. Employing an empirical legal method with a qualitative approach, data were collected through interviews and document analysis. The findings reveal that consignment functions as a legal instrument to safeguard and temporarily suspend compensation payment until a final judicial determination is reached. Supreme Court Decision Number 1675 K/Pdt/2021 affirms that the prevailing party is entitled to full land compensation as recognition of proprietary rights, while building compensation may be relinquished through a peace agreement and social compensation partially allocated. Conversely, the losing party forfeits land rights but retains full building compensation and partial social compensation based on the settlement deed. The study concludes that dispute resolution in land acquisition extends beyond final court judgments and requires non-litigation mechanisms to ensure proportional distribution of rights, thereby reinforcing legal certainty, preventing further disputes, and ensuring equitable protection in public interest development.